Compromiso con la responsabilidad social en Portugal: estudio comparativo entre las áreas metropolitanas de Lisboa y Oporto - Pache Durán, M.; Nevado Gil, T.; Paiva, I.; Carvalho, L. (Revista Española de Documentación Científica, 2021)
Social Responsibility has become a key piece for organizations. At the same time that society is increasingly demanding access to information, this becomes particularly important in the case of public organisations. The use of In-formation and Communication Technologies (ICT) is an easy and effective way for a large part of the population to access information. Organisations should therefore use this channel of communication to inform and communicate with their audience. This work aims to establish a comparison between the metropolitan areas of Lisbon and Porto of the degree of dissemination of information on Social Responsibility made by local public administrations through their webpages. To this end, a content analysis was carried out applying indicators previously tested in other territories. The results suggest that, in general, local public administrations in the two metropolitan areas are developing specific Social Responsibility policies showing the same commitment to sustainability, although the Lisbon metropolitan area seems to be more committed to environmental information.